Science Teachers and Budget Planning for Instructional Resources in Secondary Schools in Nairobi, Kenya (Asian Education Studies, 2017)
Achieving transformational knowledge based economy as provided for in Kenya’s Vision 2030, requires adequately budgeted for science instructional resources. This is because instructional resources are key in practical work which enhances learners experience and understanding science concepts, hence better learning achievement. This study sought to establish the link between budget planning in secondary schools in Nairobi County to their financial management policies in terms of setting up structures for handling budgetary allocations in a coordinated approach through consultation with staff. It relied on a sampled principals and science teachers from public and private schools in Nairobi County obtained using stratified sampling techniques. Using cognitive based participatory decision making model, the study established that secondary schools have budgeting objectives that take science instructional resources in consideration; science teachers place their budgetary request based on their schemes of work to the budgeting committee and are present during prioritization on departmental list. It also established that systems for projecting revenues and expenditures are established in secondary schools to link policy objective on science instructions and resources and that allocations for instructional resources are specified in school budget in public secondary schools than their private counterparts. In practice, the study recommended that science teachers need to be involved in budgetary decision making and measure be put in place to ensure this happen. It suggested more research on the role science teachers in improving learning outcomes through participation in budgetary decision making.